Los procedimientos administrativos sancionadores y su acción penal por incumplimiento de decisiones legítimas de autoridad competente de los procedimientos administrativos sancionadores de la dirección de justicia y vigilancia del GAD Municipal de Guayaquil - Granda Echeverría, José Darío (2024)
Determining whether or not there is compliance with the decisions of the competent authority, in the present study the analysis of whether the companies abide by the decisions is a complex job, since we have the opposition to it. The Directorate of Justice and Surveillance of the Autonomous Decentralized Municipal Government of Guayaquil has had an arduous task when carrying out its intervention at the city level, the city is really large and reaching all those administered is complex, but not impossible, and verifying the Compliance is precisely through monitoring, sanctions and other impositions such as fines, to the point of filing the corresponding complaint with the control body. Through a pure investigation, with an inductive method, which allows clear conclusions, a mixed approach in which there will be interviews and a small survey, it will seek to determine whether or not there is compliance with an order issued by a legitimate body endowed with competition, with a clear objective of verifying if there is ambiguity in the norm or lack of normative application, which will allow to have a report of compliance results or sanctions imposed.